Safety and efficacy of l‐cystine produced using Pantoea ananatis strain NITE BP‐02525 for all animal species. (28th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐cystine produced using Pantoea ananatis NITE BP‐02525 when used as a nutritional additive (amino acid) or as a sensory additive (flavouring compound) in feed and water for drinking for all animal species. l ‐Cystine is a dispensable sulfur‐containing amino acid, naturally occurring in proteins of plants and animals. The amino acid l ‐cystine produced by fermentation with P. ananatis NITE BP‐02525 is safe for all animal species, if the requirements for sulfur‐containing amino acids are respected. The maximum amount of l ‐cystine that can be safely added to the diet will depend on the levels of other sulfur amino acids. This conclusion would also cover its use as a sensory additive. The use of l ‐cystine produced by fermentation with P. ananatis NITE BP‐02525 in animal nutrition raises no safety concerns to consumers of animal products. The additive under assessment is considered slightly irritating by inhalation, not irritating to the skin or eyes and is not a skin sensitiser. There is no risk for persons handling the additive from the exposure to endotoxins by inhalation. The use of the l ‐cystine produced by fermentation with P. ananatis NITE BP‐02525 as a feed additive does not represent a risk to the environment. l ‐Cystine is considered efficacious in partially meeting the requirements of sulfur‐containing amino acids in all animal species. For the supplemental l ‐cystine to be as efficacious in ruminants as in non‐ruminant species, it would require protection against degradation in the rumen. It is also considered efficacious as a feed flavouring compound under the proposed conditions of use.